Sistem Informasi Penjualan Roti Gembong berbasis Web - Abdurrahman Luthfi; Helmi Fadhilah; Dido Muhammad Hapsah; Muhamad Hanu Mursidin; Windu Abdillah; Lantip Sidik; Estu Sinduningrum; Muhammad Fitra Ghazaly; Rafli Abadi Ikhwan (J-INTECH ( Journal of Information and Technology), 2024)
This study aims to evaluate the impact of implementing a web-based application in improving the business performance of Gembong Raja Rasa bread. Through the development of this application, it is expected to improve the efficiency of the sales process, expand market reach, and ultimately increase company revenue. This study analyses quantitative and qualitative data obtained before and after the application implementation. The measured variables include the number of transactions, average transaction value, customer satisfaction level, and operational efficiency. The results showed that the implementation of web-based applications had a significant impact on the business performance of Gembong Raja Rasa bread. There is a significant increase in the number of transactions and average transaction value after the application implementation. This shows that the application succeeded in attracting new customers and increasing the frequency of purchases of loyal customers. In addition, the customer satisfaction survey results showed a significant improvement, especially in the aspects of ease of ordering and speed of delivery. Improved operational efficiency is also evident from the reduction in the time required for order processing and inventory management.